2007
DOI: 10.1016/j.jsbmb.2006.12.050
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on mechanisms of gene regulation by 1,25-dihydroxyvitamin D3 and its receptor

Abstract: 1, (1,25(OH) 2 D 3 ) functions as a systemic signal in vertebrate organisms to control the expression of genes whose products are vital to the maintenance of calcium and phosphorus homeostasis. This regulatory capability is mediated by the vitamin D receptor (VDR) which localizes at DNA sites adjacent to the promoter regions of target genes and initiates the complex events necessary for transcriptional modulation. Recent investigations using chromatin immunoprecipitation techniques combined with various gene s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 34 publications
4
35
0
2
Order By: Relevance
“…This finding is in line with our data that only 3% of ERβ DNA-binding regions are within 1 kb from either end of genes. A similar pattern for global DNA-binding has also been shown for androgen receptor, glucocorticoid receptor, and vitamin D receptor binding to DNA (31)(32)(33). Based on these findings, an enhancer-promoter looping mechanism has been proposed for transcriptional regulation by nuclear receptors (34).…”
Section: Discussionsupporting
confidence: 60%
“…This finding is in line with our data that only 3% of ERβ DNA-binding regions are within 1 kb from either end of genes. A similar pattern for global DNA-binding has also been shown for androgen receptor, glucocorticoid receptor, and vitamin D receptor binding to DNA (31)(32)(33). Based on these findings, an enhancer-promoter looping mechanism has been proposed for transcriptional regulation by nuclear receptors (34).…”
Section: Discussionsupporting
confidence: 60%
“…To this end, we first analysed the expression of vitamin D receptor (VDR), a member of the nuclear receptor superfamily that mediates all known actions of 1,25(OH) 2 D 3 (Ordo´nez-Mora´n et al, 2008). As reported in many systems, 1,25(OH) 2 D 3 increased VDR protein (Wiese et al, 1992;Pike et al, 2007). SPRY2 did not change basal VDR expression or its increase by ligand (Figure 2c).…”
Section: 25(oh)mentioning
confidence: 82%
“…We have previously reported that auto-regulation of VDR gene expression occurs in bone cells both in vitro and in vivo (51). Mechanistically, this regulation is mediated directly through the activity of at least two enhancers, one located within a VDR gene intron and the other upstream of the TSS (52-54).…”
Section: Discussionmentioning
confidence: 99%